2020
DOI: 10.1002/eap.2145
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐temporal assessment of grassland α‐ and β‐diversity using hyperspectral imaging

Abstract: While more and more studies are exploring the application of remote sensing in assessing biodiversity for different ecosystems, most consider biodiversity at one point in time. Using several remote-sensing-based metrics, we asked how well remote sensing can detect biodiversity (both aand b-diversity) in a prairie grassland across time using airborne hyperspectral data collected in two successive years (2017 and 2018) and at different periods in the growing season (2018). The ability to detect biodiversity usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 83 publications
0
41
0
2
Order By: Relevance
“…However, also non-peak season features and RGB drone features from two different years (2016 and 2018) were important in the different regressions Figure 4. This indicates that multitemporal data can alleviate problems related to temporal mismatches and increase model performance (Räsänen et al 2020;Halabisky, Babcock, and Moskal 2018;Gholizadeh et al 2020;Poley and McDermid 2020). Nevertheless, there is some uncertainty when comparing the relative benefit of datasets with divergent spectral and spatial resolutions as the data were acquired at different times; in an ideal situation, all datasets would have been collected simultaneously.…”
Section: The Importance Of Hyperspectral and Other Remote Sensing Feamentioning
confidence: 99%
See 1 more Smart Citation
“…However, also non-peak season features and RGB drone features from two different years (2016 and 2018) were important in the different regressions Figure 4. This indicates that multitemporal data can alleviate problems related to temporal mismatches and increase model performance (Räsänen et al 2020;Halabisky, Babcock, and Moskal 2018;Gholizadeh et al 2020;Poley and McDermid 2020). Nevertheless, there is some uncertainty when comparing the relative benefit of datasets with divergent spectral and spatial resolutions as the data were acquired at different times; in an ideal situation, all datasets would have been collected simultaneously.…”
Section: The Importance Of Hyperspectral and Other Remote Sensing Feamentioning
confidence: 99%
“…In particular, with multi-source data, different aspects of the landscape, such as spectral, topographic, and vegetation height properties at multiple spatial resolutions can be captured. Thereby, the explanatory capacities are typically higher than when using a single data source Chen, Huang, and Xu 2017;Arroyo-Mora et al 2017;Luo et al 2016;Sankey et al 2018;Poley and McDermid 2020), and further boosts in model performance can be obtained with multi-temporal data (Halabisky, Babcock, and Moskal 2018;Gholizadeh et al 2020;Poley and McDermid 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the scale issue, which has shown that its increase could impact positively or negatively on SVH [17,19,21] (Schmidtlein and Fassnacht, 2017;Oldeland et al, 2010;Rocchini et al, 2004), little is known about the impact of phenology on the relationship between spectral heterogeneity and species diversity, especially in the savannah ecosystem. In an experiment in prairie grasslands, Gholizadeh et al (2020) [24] observed that a shift in phenology affected the relationship between spectral heterogeneity metrics and species richness and that the relationship between spectral heterogeneity metrics and species richness may change between years, regardless of the phenology. However, it must be noted that the experiment was conducted in an ecosystem where (i) a shift in phenology was accompanied by a change in species richness and (ii) there was prescribed burning, which might have affected the spectral reflectance, as it alters the percentage cover of individual species and the background characteristics of the landscape [24,25] (Flanagan et al, 2015;Gholizadeh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment in prairie grasslands, Gholizadeh et al (2020) [24] observed that a shift in phenology affected the relationship between spectral heterogeneity metrics and species richness and that the relationship between spectral heterogeneity metrics and species richness may change between years, regardless of the phenology. However, it must be noted that the experiment was conducted in an ecosystem where (i) a shift in phenology was accompanied by a change in species richness and (ii) there was prescribed burning, which might have affected the spectral reflectance, as it alters the percentage cover of individual species and the background characteristics of the landscape [24,25] (Flanagan et al, 2015;Gholizadeh et al, 2020). In an alpine coniferous forest, Torresani et al (2019) observed that the relationship between spectral heterogeneity and tree species diversity was highest during the summer period when the NDVI reached its peak and lowest during the winter period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation